Effects of a carbohydrate-protein beverage on cycling endurance and muscle damage - Saunders, M. J.; Kane, M. D.; Todd, M. K. (Medicine & Science in Sports & Exercise, 2004)
INTRODUCTION: The purpose of this study was to determine whether endurance cycling performance and postexercise muscle damage were altered when consuming a carbohydrate and protein beverage (CHO+P; 7.3% and 1.8% concentrations) versus a carbohydrate-only (CHO; 7.3%) beverage. METHODS: Fifteen male cyclists (mean (.-)VO(2peak) = 52.6 +/- 10.3 mL x kg x min) rode a cycle ergometer at 75% (.-)VO(2peak) to volitional exhaustion, followed 12 - 15 h later by a second ride to exhaustion at 85% (.-)VO(2peak). Subjects consumed 1.8 mL x kg BW of randomly assigned CHO or CHO+P beverage every 15 min of exercise, and 10 mL x kg BW immediately after exercise. Beverages were matched for carbohydrate content, resulting in 20% lower total caloric content per administration of CHO beverage. Subjects were blinded to treatment beverage and repeated the same protocol seven to 14 d later with the other beverage. RESULTS: In the first ride (75% (.-)VO(2peak)), subjects rode 29% longer (P < 0.05) when consuming the CHO+P beverage (106.3 +/- 45.2 min) than the CHO beverage (82.3 +/- 32.6 min). In the second ride (85% (.-)VO(2peak)), subjects performed 40% longer when consuming the CHO+P beverage (43.6 +/- 12.5 min) than when consuming the CHO beverage (31.2 +/- 8.7 min). Peak postexercise plasma CPK levels, indicative of muscle damage, were 83% lower after the CHO+P trial (216.3 +/- 122.0 U x L) than the CHO trial (1318.1 +/- 1935.6 U x L). There were no significant differences in exercising levels of (.-)VO(2), ventilation, heart rate, RPE, blood glucose, or blood lactate between treatments in either trial. CONCLUSION: A carbohydrate beverage with additional protein calories produced significant improvements in time to fatigue and reductions in muscle damage in endurance athletes. Further research is necessary to determine whether these effects were the result of higher total caloric content of the CHO+P beverage or due to specific protein-mediated mechanisms.